Enteric Nervous System and Esophageal-Gastrointestinal Motility in Experimental Congenital Diaphragmatic Hernia - Pederiva, Federica; Martinez, Leopoldo; Tovar, J. A. (European Journal of Pediatric Surgery, 2014)
Gastroesophageal reflux and intestinal distension have been described in survivors of congenital diaphragmatic hernia (CDH). Deficient enteric innervation demonstrated in experimental models is a likely explanation for these symptoms. This study aimed at further characterizing these anomalies and examining esophageal and intestinal motility in this condition. Pregnant rats received either nitrofen or vehicle on E9.5. Sections of E15, E18, and E21 esophagus and small bowel were stained for protein gene product 9.5, nicotinamide adenine dinucleotide phosphate (NADPH) diaphorase (NADPHd), and acetylcholinesterase (AChE). The proportion of neural tissue/muscle surface was measured and the NADPHd- and AChE-positive motor endplates (MEPs) were counted. E18 and E21 stomachs were stained for AChE, the ganglia were counted and measured. The peristalsis of the esophagus and small bowel was video recorded. The relative neural/muscle surface and the number of NADPHd- and AChE-positive MEPs were decreased on E15 and E18 in the esophagus and small bowel of embryos with CDH, but they tended to improve on E21. The number and the mean surface of stomach ganglia were smaller in E18 and E21 fetuses with CDH. Peristaltic movements were decreased in the esophagus and small bowel of animals with CDH. Deficient enteric innervation impaired gastrointestinal motility in experimental CDH. This could explain some long-term morbidity in the human condition.
Keywords: diaphragmatic hernia; enteric nervous system; peristalsis